Household Use of Financial Planners: Measurement Considerations for Researchers - Heckman, Stuart J.; Seay, Martin C.; Kim, Kyoung Tae; Letkiewicz, Jodi C. (My University, 2017)
Using the Certified Financial Planner (CFP) Board’s definition of financial planning, this paper evaluates the validity of the measures of financial planner use in publicly available datasets. A review of Financial Services Review, Journal of Personal Finance, Journal of Financial Planning, Journal of Family and Economic Issues, Journal of Consumer Affairs, and Journal of Financial Counseling and Planning identified seven datasets that were commonly used to investigate financial planner use. Of these, the two most promising measures were found in the Survey of Consumer Finances and the National Longitudinal Study of Youth (1979). However, an evaluation of these measures raises significant concerns related to their validity. This article critically evaluates these measures and provides insights into the development of better measures of financial planner use for the future.
Citation: Heckman, Stuart J. and Seay, Martin C and Kim, Kyoung Tae and Letkiewicz, Jodi, Household Use of Financial Planners: Measurement Considerations for Researchers (November 2, 2016). Financial Services Review, Vol. 25, p. 427-446, 2016.
Keywords: Financial Planner Use; Financial Advice; Measurement